Antibiotic prescription patterns in patients with suspected urinary tract infections in Ecuador. - Xavier Sánchez; Alicia Latacunga; Iván Cárdenas; Ruth Jimbo-Sotomayor; Santiago Escalante (PLoS ONE, 2023)
Background Urinary tract infections (UTI) are among the most common cause to prescribe antibiotics in primary care. Diagnosis is based on the presence of clinical symptoms in combination with the results of laboratory tests. Antibiotic therapy is the primary approach to the treatment of UTIs; however, some studies indicate that therapeutics in UTIs may be suboptimal, potentially leading to therapeutic failure and increased bacterial resistance. Methods This study aimed to analyze the antibiotic prescription patterns in adult patients with suspected UTIs and to evaluate the appropriateness of the antibiotic prescription. This is a cross-sectional study of patients treated in outpatient centers and in a second-level hospital of the Ministry of Public Health (MOPH) in a city in Ecuador during 2019. The International Classification of Disease Tenth Revision (ICD-10) was used for the selection of the acute UTI cases. The patients included in this study were those treated by family, emergency, and internal medicine physicians. Results We included a total of 507 patients in the analysis and 502 were prescribed antibiotics at first contact, constituting an immediate antibiotic prescription rate of 99.01%. Appropriate criteria for antibiotic prescription were met in 284 patients, representing an appropriate prescription rate of 56.02%. Less than 10% of patients with UTI had a urine culture. The most frequently prescribed antibiotics were alternative antibiotics (also known as second-line antibiotics), such as ciprofloxacin (50.39%) and cephalexin (23.55%). Factors associated with inappropriate antibiotic prescribing for UTIs were physician age over forty years, OR: 2.87 (95% CI, 1.65-5.12) p<0.0001, medical care by a general practitioner, OR: 1.89 (95% CI, 1.20-2.99) p = 0.006, not using point-of-care testing, OR: 1.96 (95% CI, 1.23-3.15) p = 0.005, and care at the first level of health, OR: 15.72 (95% CI, 8.57-30.88) p<0.0001. Conclusions The results of our study indicate an appropriate prescription rate of 56.02%. Recommended antibiotics such as nitrofurantoin and fosfomycin for UTIs are underutilized. The odds for inappropriate antibiotic prescription were 15.72 times higher at the first level of care compared to the second. Effective strategies are needed to improve the diagnosis and treatment of UTIs.